Inquiries into the Cognitive and Affective Domains of Learning - Suzanne Porath (Networks: An Online Journal for Teacher Research, 2020)
In this issue of Networks, we see educator-researchers inquire into the cognitive aspects of their students’ learning, but also explore the affective aspects of learning such as engagement, choice, and personal response.
Keywords: editorial introduction; affective domain; cognitive domaine; teacher research; action research